Students’ Preferences for Contexts and their Relevance to School Mathematics in Malawi - Kazima, Mercy (African Journal of Research in Mathematics, Science and Technology Education, 2013)
This paper looks at mathematics and its relevance in schools from the perspective of students' interests. It starts by discussing briefly the importance of paying attention to cultural and social relevance, and then it focuses on students' interests as one of the aspects of relevance. Findings are presented from a survey conducted in Malawi with 346 secondary school students. The study explored what students would find interesting to learn as contexts in school mathematics by indicating their preferences for some given contexts in form of a questionnaire, which was adapted from a very large cross country project (ROSME). Findings include that students are interested in mathematics for future careers and mathematics of modern technologies more than ethnomathematics and mathematics of agriculture, and there are no differences in preferences for contexts between female and male students. Most of the findings confirm findings from previous ROSME studies, particularly those situated in African countries, and therefore strengthen the arguments made earlier by these studies. This paper further argues that relevance for students includes their interests, and therefore should be considered as a factor in the development of curriculum materials and classroom activities.
Keywords: _C:Malawi MWI